2017
DOI: 10.1117/1.jbo.22.4.045007
|View full text |Cite
|
Sign up to set email alerts
|

Portable LED-induced autofluorescence spectroscopy for oral cancer diagnosis

Abstract: Oral cancer is a serious and growing problem in many developing and developed countries. To improve the cancer screening procedure, we developed a portable light-emitting-diode (LED)-induced autofluorescence (LIAF) imager that contains two wavelength LED excitation light sources and multiple filters to capture ex vivo oral tissue autofluorescence images. Compared with conventional means of oral cancer diagnosis, the LIAF imager is a handier, faster, and more highly reliable solution. The compact design with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Coincidently, Yan et al 13 had just reported a new attempt of objective methods of EVINCE by calculating ROC curve, area under the curve, and regions of interest, whose methods were similar to ours and their concept was probably based on same intensions to ours. Having said that, there are three different points from our study in addition to difference of devices as follows; (1) our study proposed comparison of three modalities (the subjective and objective AVM of VELscope and IOM); (2) our study also proposed comparison of LNR between different histopathological diagnosis; and (3) the first step of examination was performed just before biopsy, which is not chair-side usage of the device.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Coincidently, Yan et al 13 had just reported a new attempt of objective methods of EVINCE by calculating ROC curve, area under the curve, and regions of interest, whose methods were similar to ours and their concept was probably based on same intensions to ours. Having said that, there are three different points from our study in addition to difference of devices as follows; (1) our study proposed comparison of three modalities (the subjective and objective AVM of VELscope and IOM); (2) our study also proposed comparison of LNR between different histopathological diagnosis; and (3) the first step of examination was performed just before biopsy, which is not chair-side usage of the device.…”
Section: Discussionsupporting
confidence: 62%
“… 7 , 9 , 10 , 11 , 12 Recently, several optical imaging system have been produced such as Visually Enhanced Lesion scope (VELscope, White Rock, BC, Canada), EVINC (MMOptics, São Carlos, Brazil), and Identifi 3000 (DentalEZ Inc, Malvern, PA, USA), using different wavelength of light sources. 11 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Autofluorescence is used in a fast and non-invasive method for detecting malignant and premalignant lesions. Many new diagnostic techniques and instruments are routinely used; they include Vizi-Lite (Zila Pharmaceuticals, Phoenix, AZ), Identafi (DentalEZ, PA, USA), Narrow band imaging (NBI; Olympus Medical Systems Corporation, Tokyo, Japan) and VELscope (LED Medical Diagnostics Inc., Burnaby Canada) [34,35]. Vizi-Lite is an old device that is based on chemical autofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopic criteria for skin cancer detection in situ, such as increased vascularity, the presence of pigmentation, ulceration, inflammation and keratinization are related to the appearance of unique autofluorescence features of biological tissue . The method of autofluorescence has already been shown to improve the identification of primary BCC and SCC lesions that may not be visible to the naked eye or dermoscopy . Considering the criteria for non‐melanoma skin cancer identification, healthy skin has intense green autofluorescence whereas cancerous areas may appear darker .…”
Section: Introductionmentioning
confidence: 99%